Exploring Tourist Experience in Gorontalo through Social Media Data: A Netnographic Approach - Srilian Laxmiwaty Dai; Vidhia Agmareina Hirto; Mega Sukma; Zulhajnie Wildayanti Limpas; Rahman (Jurnal Internasional Riset Bisnis Pariwisata, 2026)
This study explores tourist experiences in Gorontalo through social media narratives, employing a netnographic approach to capture the meanings embedded in user-generated content (UGC). As emerging destinations increasingly rely on digital visibility, understanding how experiences are constructed and communicated online becomes critical. This research analyses approximately 750 posts from Instagram, TikTok, and Twitter (X), focusing on textual captions, comments, and visual context to identify key experiential patterns. The findings reveal four dominant dimensions of tourist experience: natural immersion, cultural encounter, emotional resonance, and infrastructural negotiation. Tourists frequently frame Gorontalo as a hidden paradise, emphasising marine biodiversity, authentic local interactions, and a sense of tranquillity and personal restoration. These narratives highlight the interplay between cognitive and affective dimensions of experience, where physical attributes and emotional responses are co-constructed through digital storytelling. At the same time, the presence of infrastructural challenges introduces a nuanced perspective, suggesting that limitations in accessibility and facilities are often interpreted as part of the destination authenticity rather than purely negative attributes. The study contributes theoretically by extending the understanding of tourist experience as a multi-dimensional and socially constructed phenomenon within digital environments. It introduces the concept of experiential authenticity in emerging destinations and demonstrates the value of netnography in capturing lived experiences through naturally occurring data. Practically, the findings offer insights for destination managers to develop sustainable, experience-based tourism strategies while leveraging social media narratives. Overall, this research highlights the role of digital platforms in shaping how tourist experiences are produced, shared, and interpreted in contemporary tourism.